Effect of uric acid reduction on chronic kidney disease. Systematic review and meta-analysis - Casanova, Alfredo G.; Morales, Ana I.; Vicente-Vicente, Laura; López-Hernández, Francisco J. (Frontiers in Pharmacology, 2024)
Accumulating evidence suggests that hyperuricemia is a pathological factor in the development and progression of chronic kidney disease. However, the potential benefit afforded by the control of uric acid (UA) is controversial. Individual studies show discrepant results, and most existing meta-analysis, especially those including the larger number of studies, lack a placebo or control group as they aim to compare efficacy between drugs. On these grounds, we performed a me-ta-analysis restricted to studies including the action of any anti-gout therapies referenced to a control or placebo arm. This approach allows for a clearer association between UA reduction and renal effect. Of the twenty-nine papers included, most used allopurinol and febuxostat and, therefore, solid conclusions could only be obtained for these drugs. Both were very effective in reducing UA, but only allopurinol was able to significantly improve glomerular filtration rate (GFR), although not in a dose-dependent manner. These results raised doubts as to whether it is the hypouricemic effect of anti-gout drugs, or a pleiotropic effect, what provides protection of kidney function. Accordingly, in a correlation study that we next performed between UA reduction and GFR improvement, no association was found, which suggests that additional mechanisms may be involved. Of note, most trials show large inter-individual response variability, probably because they included patients with heterogeneous phenotypes and pathological characteristics, including different stages of CKD and comorbidities. This highlights the need to sub classify the effect of UA-lowering therapies according to the pathological scenario, in order to identify those CKD patients that may benefit most from them.